(untitled) (مجلة الواحات للبحوث والدراسات, 2017)
In this article, the idea of suicide is depicted along Hemingway’s writings. A sample of Ernest Hemingway stories about a character he called Nick Adams will be studied. Hemingway gave the hero of so many of his early stories the name of "Nick Adam portraying in various collections. The study proved to be plausible only after Hemingway’s death, in 1972, when the stories were collected, arranged in the chronological order of Adams’ life which were found after Hemingway’s death. It will be revealed that the paths towards suicide were clearly seen on the ground of the Hemingway’s narratives. And the closer his steps towards suicide, the deeper his footsteps were in the land of his writings. Key words - Death, Steps, Stories, Suicide.